Beauty Vloggers Influence: Enhancing Consumer Trust and Purchase Decisions for Make Over Product - Pantjolo Giningroem, Dewi Sri Woelandari; Setyawati, Novita Wahyu; Navanti, Dovina; Rohaeni, Heni; Yuniati, Triana (Magister Manajemen of Universitas Islam Nahdlatul Ulama Jepara, 2024)
This research aims to explore the influence of the attractiveness of beauty vloggers and consumer trust as social media promotional strategies on purchasing decisions for Make Over product through purchase intention. This research uses a quantitative approach with convenience sampling techniques on 200 respondents. The analysis technique used in this research is Structural Equation Modeling (SEM) with the Smart PLS version 4.0 statistical tools. The research results show that the attractiveness of beauty vloggers and consumer trust have a significant effect on purchasing interest, furthermore the attractiveness of beauty vloggers does not influence purchasing decisions. Meanwhile, consumer trust influences purchasing decisions and purchasing interest also has a significant influence on purchasing decisions. The attractiveness of beauty vloggers and consumer trust have a significant influence on purchasing decisions through purchasing interest as an intervention.